NAUM EITINGON AND THE ACTIVITY OF THE SOVIET SECRET SERVICES IN SPAIN AND MEXICO IN THE FIRST HALF OF THE TWENTIETH CENTURY - Bács, Zoltán György (POLARITIES, 2023)
Naum Eitingon’s life and carrier give an excellent example of the practical implementation of the export of the revolution, an essential postulate of the Bolcheviks’ revolutionary theory. In order to achieve the universal victory of the Communist revolution the Soviet government supported movements abroad having the same views and also planned and implemented covert operations in many countries. One of the scenes of these operations was Spain during the Civil War. Eitingon and other Soviet operatives played an active role in stealing and transferring the golden reserve of the Spanish Central Bank to the Soviet Union. Another theater of operation of the Soviet secret services and personally Eitingon’s became Mexico, where Leon Trotskiy found asylum after had been expelled from Moscow. Eitingon was a key protagonist in preparing and carrying out the assassination of Stalin’s most feared opponent. The aim of the present study is to introduce this person into the Hungarian Hispanist and Latinamericanist historiography where he has been barely noticed up to the current days.